Concentration of organotin and booster biocides in sediments of seagrass area from Sungai Pulai estuary, south of Johor, Malaysia - Mukhtar, 'Aqilah; Mohamat Yusuff, Ferdius @ Ferdaus; Zulkifli, Syaizwan Zahmir; Harino, Hiroya; Ismail, Ahmad; Inoue, Koji (MDPI, 2019)
Antifouling compounds are widely used in paints applied on ship hulls to prevent attachment of fouling organisms. However, a certain amount of these chemicals could leach from the painted surface, enter seawater, and pose deleterious effects on various marine biotas. The present study aimed to determine the concentration of organotin (OT) compounds and booster biocides in sediments collected from the seagrass area of Sungai Pulai estuary, Malaysia. The sediment samples were collected from three points on the seagrass bed, brought back to the laboratory, extracted using standard extraction procedure, and the analytes were analysed using gas chromatography-mass spectrometry (GC-MS) method. The results showed that tributyltin (TBT) concentrations in sediments were within the range of 8.1 ± 0.4 to 10.6 ± 0.5 µg/kg, whereas the values of triphenyltin (TPT) were between 17.1 ± 0.9 and 19.4 ± 1.0 µg/kg. The range of concentration of booster biocides, namely diuron, dichlofluanid chlorothalonil, Irgarol 1051, M1, and Sea-Nine 211, were from <0.1 to 22.9 ± 1.1, 48.7 ± 2.4 to 800 ± 40, <0.1 to 6.2 ± 0.3, <0.1 to 1.4 ± 0.1, 44 ± 2.2 to 877 ± 44, and 9.1 ± 0.5 to 170 ± 8.5 µg/kg, respectively. The concentration of organotin was much lower than the previous study conducted in southern Johor. Meanwhile, the increased concentration of booster biocides proves the use of these compounds as antifouling paints in shipping systems nowadays.